Influence of growing season, shading screen and mulching on growth, development and quality of gladiolus - Becker, Dislaine; Paulus, Dalva (Seven Editora, 2023)
To reduce the risks associated with the production of gladiolus flowers in the climatic conditions of southwestern Paraná, Brazil, this study characterized the growth, development, and floral stem quality of plants cultivated under different-colored shade nets and mulching in four growing seasons. The gladiolus cultivar ‘White Goddess’ was grown in beds with and without mulching in the soil. Three shade nets individually stained black, silver, and red all with 35% shading, were used in this study, and an additional treatment (control) in which plants were grown in full sun. Growth (LAI and height), development (cycle in days, and degree days), and flower quality (size and damaged stem) were evaluated in eight plants in each treatment. Plants were distributed in a randomized block design in a factorial scheme (season x mulching x shade screen). The cycle ranged from 66 to 89 days and 1732 to 1268°C day. The mean difference in the cycle between treatments was 3 days. Less flower stem damage happened under the silver net and more in full sun. The shading net associated with mulching favored the growth characteristics of the plants, and in autumn, the flowers had the highest quality standard. DOI: https://doi.org/10.56238/devopinterscie-136